Impact of country-of-origin and price on product's advertisement efficacy (2010)
The objective of this study is to assess the effect that country-of-origin and price have on efficacy of advertisements for a product. The African population has noticeably not featured much in country-of-origin research in spite of the growing size and complexity of the African consumer market. Country-of-origin refers to the country of manufacture, production, or growth where an article or product comes from. In realizing the goals for which it was set to achieve, this experimental study ascertained the influence of country-of-origin and price on advertisement efficacy involving an African population sample. Six hundred female and male undergraduates (with mean age =23.02; SD= 3.2 years) were randomly drawn from a large university, to view a product advertisement that uniquely manipulated country-of-origin and price for a fictitious brand of insecticide named "Anti sect." Data analysis was done using one-way analysis of variance. It was found that individually and collectively, country-of-origin and price did affect advertisement efficacy significantly. It was concluded that advertisers need to consider product's country of- origin and product's price when developing successful advertisement campaigns. Beyond advertisements, country of- origin and price also matter to buyers and consumers of products.